Absolute dosimetry for FLASH proton pencil beam scanning radiotherapy - Ana Lourenço; Anna Subiel; Nigel Lee; Sam Flynn; John Cotterill; David Shipley; Francesco Romano; Joe Speth; Eunsin Lee; Yongbin Zhang; Zhiyan Xiao; Anthony Mascia; et al. (Scientific Reports, 2023)
Abstract A paradigm shift is occurring in clinical oncology exploiting the recent discovery that short pulses of ultra-high dose rate (UHDR) radiation—FLASH radiotherapy—can significantly spare healthy tissues whilst still being at least as effective in curing cancer as radiotherapy at conventional dose rates. These properties promise reduced post-treatment complications, whilst improving patient access to proton beam radiotherapy and reducing costs. However, accurate dosimetry at UHDR is extremely complicated. This work presents measurements performed with a primary-standard proton calorimeter and derivation of the required correction factors needed to determine absolute dose for FLASH proton beam radiotherapy with an uncertainty of 0.9% (1 $$σ$$ σ ), in line with that of conventional treatments. The establishment of a primary standard for FLASH proton radiotherapy improves accuracy and consistency of the dose delivered and is crucial for the safe implementation of clinical trials, and beyond, for this new treatment modality.